Strategi Rintisan Pariwisata Terintegrasi dan Berkelanjutan di Kota Semarang - Trimartuti, Nana Kariada; Prajanti, Sucihatiningsih Dian Wisika; Rahayuningsih, Margareta; Sidiq, Wahid Akhsin Budi Nur; Mutiatari, Dhita Prasisca (Badan Riset dan Inovasi Daerah Kota Semarang, 2022)
Gunungpati District has an ex-JSDF land area of 73.2 ha consisting of 67 parcels of land spread across 12 Sub-Districts. The ex-JSDF land area was originally a poverty alleviation program and critical land conservation in the City of Semarang in collaboration with the JSDF (Japanese Social Development Fund), Worldbank and the City Government of Semarang. The development of several ex-JSDF land locations has developed into agro-tourism areas such as those managed by the Agriculture Service in Cepoko Village. However, several other locations managed by farmer groups were abandoned and then experienced land conversion. So that the potential of the ex-JSDF in the region was identified to obtain a pilot strategy for sustainable tourism in the city of Semarang. The research was carried out by identifying tourist attractions and tourism development factors so that directions for developing integrated and sustainable tourism areas in Gunungpati District could be obtained. the results of the analysis of the suitability of cultivated land in the former JSDF land locations spread across 12 sub-districts, 11 of which have an S1 suitability class, namely its use is very suitable for cultivating fruit crops. Meanwhile, one other location, namely Sumurrejo Village, has a Masters degree of suitability (quite appropriate). In general, the limiting factors in the heavy research sites were soil texture and fertility which were in class S3. Another mild limiting factor is temperature and groundwater productivity which are in class S2. Sustainability analysis found that the level of sustainability of fruit cultivation on ex-JSDF land in the Gunungpati District area was in a less sustainable status, the resulting index value only reached 58.94. Integrated tourism development area in Kec. Gunungpati with the main tourism zones covering, 1) Agroeduwisata Kandri Tourism Village, 2) Kreo Cave & Jatibarang Reservoir, 3) Kandri Boat Tourism, 4) Ngrembel Asri, and 5) Firdaus Fatimah Zahra.